WOMEN’S EXPERIENCES IN THE GREEN ECONOMY PROGRAM AT BUMDESMA A PHENOMENOLOGICAL STUDY FROM PSYCHOLOGICAL, MOTIVATIONAL, AND ENVIRONMENTAL AWARENESS PERSPECTIVES - Ahmad Balya, Toifur; Mufarrochah, Siti; Mu’di, Ahmad (Seminar Nasional dan Call For Paper 2025 dengan tema "Inovasi Inklusif Gender dalam Sociopreneurship" PSGESI LPPM UWP, 2025)
This study explores the experiences of women participating in the Green Economy Program at BUMDESMA in Kedamean, Gresik, using a phenomenological approach. The research focuses on psychological aspects, motivation, environmental awareness, and empowerment, aiming to understand the subjective experiences of women involved in sustainable economic activities. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically to identify patterns of participation, motivation, and the impact of involvement. The findings reveal that women actively engage in activities such as processed food production, environmentally friendly crafts, and waste management through bank sampah initiatives. Their participation enhances skills, self-confidence, personal satisfaction, decision-making abilities, and social roles, while also strengthening environmental awareness and community solidarity. Motivation arises from intrinsic drives for economic independence, family welfare, and environmental care, supported by social interaction within the community. These results align with previous studies highlighting women’s roles in ecofeminism, environmental stewardship, and green economy initiatives, confirming that structured programs like BUMDESMA not only foster environmental and economic benefits but also empower women socially and psychologically. The study emphasizes the importance of participatory and sustainable approaches in understanding women’s experiences and aspirations in local-level green economy programs